2012
DOI: 10.1186/1756-3305-5-113
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification enzymes associated with insecticide resistance in laboratory strains of Anopheles arabiensis of different geographic origin

Abstract: BackgroundThe use of insecticides to control malaria vectors is essential to reduce the prevalence of malaria and as a result, the development of insecticide resistance in vector populations is of major concern. Anopheles arabiensis is one of the main African malaria vectors and insecticide resistance in this species has been reported in a number of countries. The aim of this study was to investigate the detoxification enzymes that are involved in An. arabiensis resistance to DDT and pyrethroids.MethodsThe det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 57 publications
(70 reference statements)
4
71
0
Order By: Relevance
“…The PBO exposure data support previous analyses implicating monooxygenasemediated detoxification as the primary mode of pyrethroid resistance in An. arabiensis at Mamfene, 7,17,18 because PBO enhances insecticide toxicity by providing an alternative substrate for monooxygenases. PBO pre-exposure assays can therefore be used to elucidate monooxygenasebased resistance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The PBO exposure data support previous analyses implicating monooxygenasemediated detoxification as the primary mode of pyrethroid resistance in An. arabiensis at Mamfene, 7,17,18 because PBO enhances insecticide toxicity by providing an alternative substrate for monooxygenases. PBO pre-exposure assays can therefore be used to elucidate monooxygenasebased resistance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Insecticide exposures were conducted on multiple strains of pyrethroid-resistant mosquitoes, including the major malaria vectors Anopheles arabiensis (27)(28)(29), Anopheles funestus (30,31), and Anopheles gambiae s.s. (32, 33) with well-defined mechanisms and levels of resistance, using standard WHO resistance assays with 0.05% deltamethrin papers (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…[21,41] Microarray analysis of a DDT and pyrethroidresistant laboratory colony, which was established using wild-caught material from Mamfene, revealed over-transcription of 20 genes associated with the DDT/pyrethroid resistance phenotype. [42] Most of these genes are monooxygenases and glutathione s-transferases. It is interesting to note that although no knockdown resistance (kdr) mutations have ever been recorded in wild An.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…Association analyses revealed that DDT and permethrin resistance in this laboratory colony is closely linked to the L1014F mutation while deltamethrin resistance is primarily based on enzyme detoxification. [42] …”
Section: Mechanisms Of Resistancementioning
confidence: 99%